PERLINDUNGAN HUKUM TERHADAP RECIPIENT DARI PENDONOR DARAH PENDERITA HUMAN IMMUNODEFICIENCY VIRUS (HIV) - Rahman, Arief; Chomariah, Chomariah; Pranomo, Agung (Kertha Semaya : Journal Ilmu Hukum, 2024)
Penelitian ini bertujuan mengkaji dan menganalisis perlindungan hukum terhadap recipient dari pendonor darah penderita human immunodeficiency virus (HIV). Penelitian ini merupakan studi hukum normatif dengan dua pendekatan: pendekatan hukum dan konseptual. Temuan penelitian menunjukkan bahwa perlindungan hukum bagi penerima yang terinfeksi HIV terbagi menjadi aspek preventif dan punitif. Perlindungan preventif melibatkan kewajiban PMI untuk melakukan pemeriksaan darah dan RS untuk menetapkan Prosedur Operasional Standar (SOP) untuk keamanan dalam proses transfusi darah. Sementara itu, perlindungan hukum punitif mencakup sanksi terhadap PMI dan RS jika kelalaian mereka terbukti menyebabkan kerugian pada penerima. Tanggung jawab PMI dan RS atas kerugian yang dialami oleh penerima yang terinfeksi HIV didasarkan pada prinsip tanggung jawab berdasarkan kesalahan. PMI dapat menghadapi sanksi administratif jika kelalaiannya menyebabkan infeksi HIV pada penerima. Bagi personel kesehatan di RS, penerima dapat mengejar mediasi atau mengajukan gugatan perdata untuk mencari kompensasi jika mereka terinfeksi HIV akibat kelalaian atau kesalahan. The case of a blood recipient contracting Human Immunodeficiency Virus (HIV) during a blood transfusion is a serious issue, particularly in the context of legal protection for the recipient. Therefore, two research questions are posed: 1) How is the legal protection for recipients from blood donors with HIV examined from the perspective of laws and regulations in Indonesia? and 2) How can the Indonesian Red Cross (PMI) and the Hospital (RS) be held responsible for the losses suffered by recipients if the received blood is infected with Human Immunodeficiency Virus (HIV)?. This research is a normative legal study with two approaches: legal and conceptual approaches. Research findings indicate that legal protection for recipients infected with HIV is divided into preventive and punitive aspects. Preventive protection involves the obligation of PMI to conduct blood screening and for the RS to establish Standard Operating Procedures (SOPs) for safety in the blood transfusion process. Meanwhile, punitive legal protection includes sanctions against PMI and RS if their negligence is proven to have caused harm to the recipient. The responsibility of PMI and RS for the losses incurred by recipients infected with HIV is based on the principle of liability based on fault. PMI can face administrative penalties if its negligence leads to HIV infection in the recipient. For healthcare personnel in the RS, recipients can pursue mediation or file a civil lawsuit to seek compensation if they are infected with HIV due to negligence or errors.